Retoryka i socjo-retoryka w lekturze tekstów Nowego Testamentu Cz. 1: Retoryka i nowe podejście do tradycji ustnej - Kowalski, Marcin (The Biblical Annals, 2016)
In the present article, the author argues for the usefulness and importance of rhetoric and socio-rhetoric for the reading of the New Testament texts. Part I is dedicated to the rhetorical approach. The point of departure are the remarks of the Pontifical Biblical Commission on the questionable rhetorical education of biblical authors, on may kinds of rhetoric, and on the limited applicability of rhetoric to the analysis of biblical text. The author answers the objections raised against the rhetorical method and argues for the use of Greco-Roman rhetoric as the compositional instrument closest to the cultural milieu of the New Testament authors. The Greco-Roman rhetoric presents itself as the best tool to explore the texture of biblical writings characterized by high residual orality. To substantiate it, the author shows the recent change of paradigm in the approach to the oral tradition and textuality in the Bible. Part I of the article finishes with the elaboration and exposition of the basic steps of rhetorical analysis proposed by George A. Kennedy.